Construindo uma nova ordem: o debate educacional na Assembléia Constituinte de 1823 - Ferronato, Cristiano de Jesus (2006)
The objective of this work is to analyze the debates of the constituents of 1823 around the projects that had as intention the organization of the education in Brazil. With the end of the Portuguese domain the Brazil was around with the organization of a structure that gives contours of a Nation. Among these was the organization of an educational plan" so that the children of the elite could be part of the public administration and then to command the destinations of the Imperial State searching to strengthen its regional powers. For the analysis of the works of the constituent members of the House of Representatives as regards to the education we use as main source the Constituent Assembly Annals of 1823, besides others written contemporaries to the period. The adopted methodology was the bibliographical research (documental and historiographical) and the analysis and interpretation of the extracted information. The research involved the analysis in the literal and interstitial plans. Moreover, as the speeches and debates of the constituent members of the House of Representatives they do not form a closed universe, they only gain intelligibility if articulated with the widest historical reality of that moment. The systematic development of the studies made the research circulate between the internal plans (the specific questions of the Brazilian society of that time) and external (the action of forces and ideas originating of the exterior with which Brazil interacted). On the other hand, as the education constitutes a field that, although has its own peculiarities, it does not have absolute autonomy in relation to all of the social life we always search the articulation of the educational question with the other aspects of the society that interact more directly with it (ideology, economy, politics, culture, social relations, etc...). Finally as we talked about a discussion located in one historical moment that involves one given complexity, became inevitable and imperative the dialogue with the pertinent historiography in order to confront hypotheses and to enrich the analysis of the documentary source used in the research.